89 End of life care and cognitive impairment: a quality improvement study. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Powell, Amanda; Boa, Sally; Foster, Gillian
Abstract : Background: A hospice retrospective in-patient case notes review explored care provision at the end of life, mapped against the four key principles in the Scottish Government guidance. Most patients had documentation of informative, sensitive and timely discussions about dying, and exploration of their fears, concerns, goals, wishes, and social, spiritual and psychological needs. However, this was less likely if patients had cognitive impairment. Aim: To understand from staff caring for patients with cognitive impairment in a hospice in-patient unit, what prevents them from exploring and documenting their wider holistic needs. Methodology: A qualitative study was undertaken, interviewing in-patient hospice medical and nursing staff, using the 5 Whys tool. Results were analysed using a framework analysis approach. Results: Fifteen staff members were interviewed – five doctors, five registered general nurses and five healthcare assistants. Themes that emerged included: confidence and skills when communicating with cognitively impaired patients and their informal carers; the importance of familiarity and developing relationships over time; that physical care tended to take priority over time spent exploring issues especially when time was limited. Reasons for not exploring and documenting were common for all staff groups. Conclusions and recommendations: The results were presented to the wider hospice team who made suggestions for change. These included: offering additional staff education and training in communicating with cognitively impaired people; proactively consulting informal carers to gain a deeper understanding of patients' needs; the use of a person-centred document for informal carers to complete with patients if able, that encouraged identification and exploration of psycho-social concerns; using routine handovers to highlight when these areas had not been addressed. A working group will be formed to implement and test changes to practice as part of the quality improvement in this area.